2020
DOI: 10.3390/ijms21217912
|View full text |Cite
|
Sign up to set email alerts
|

Hevein-Like Antimicrobial Peptides Wamps: Structure–Function Relationship in Antifungal Activity and Sensitization of Plant Pathogenic Fungi to Tebuconazole by WAMP-2-Derived Peptides

Abstract: Keywords: hevein-like antimicrobial peptides; antifungal activity; antifungal determinants; synergy; chemosensitization; tebuconazole; plant pathogenic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 73 publications
(125 reference statements)
3
26
0
Order By: Relevance
“…The obtained results showed F. oxysporum was significantly more sensitive to WAMP-N and WAMP-G2 than to other peptide fragments (Table 1). The results also indicated the entire WAMP-2, the activity of which was determined earlier under the same conditions [44], had a lower inhibitory effect than either of these more active fragments. WAMP-G1 possessed no antifungal activity towards this fungus; the minimum fungicidal concentration (MFC) exceeded 10,000 µg/mL.…”
Section: Enhancement Of the Fungicidal Effect Bysupporting
confidence: 63%
See 2 more Smart Citations
“…The obtained results showed F. oxysporum was significantly more sensitive to WAMP-N and WAMP-G2 than to other peptide fragments (Table 1). The results also indicated the entire WAMP-2, the activity of which was determined earlier under the same conditions [44], had a lower inhibitory effect than either of these more active fragments. WAMP-G1 possessed no antifungal activity towards this fungus; the minimum fungicidal concentration (MFC) exceeded 10,000 µg/mL.…”
Section: Enhancement Of the Fungicidal Effect Bysupporting
confidence: 63%
“…Microconidia of the pathogen were treated to each of the WAMP-2 fragments taken at three or four concentrations ranging between 50 and 200 (WAMP-N, WAMP-G2), 100 and 400 (WAMP-G1), or 50 and 400 (WAMP-C) µg/mL. The prior research showed these concentrations were marginally or low toxic for the fungus [44]. After the treatments, the rate of germinated conidia was determined, expressed as the percent relative to the total number of conidia counted (500 ones per treatment).…”
Section: Enhancement Of the Fungicidal Effect Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Many strategies have been proposed, among which peptides play an important role [ 17 ]. Interestingly, a similar target effect is a characteristic of AMPs with lectin-like functions (e.g., defensins [ 18 ] and hevein-like peptides [ 19 ], which can bind to N-glycosylated sites of the viral spike protein or the receptor, which ultimately prevents penetration of the virus into the host cell [ 20 , 21 ]. In general, as will be described below, AMPs have great potential for effective use in the therapy of coronavirus infection [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first research step to search for chemosensitizing compounds is the in vitro testing of the antifungal effect of putative sensitizers to determine their working concentration range and to make sure their toxicity is significantly lower than that of a fungicide used against the target pathogen. Recently, we found non-fungitoxic metabolites of plant origin, which enhanced the sensitivity of five cereal pathogens to one of DMI-fungicides [27]. Earlier, we also screened a range of microbial metabolites for sensitizing activity and briefly reported that a secondary metabolite of Penicillium citrinum, 6-demethylmevinolin (6-DMM) was the most promising as a putative sensitizer among them.…”
Section: Introductionmentioning
confidence: 99%